Short-term and long-term Interconnectedness of stock returns in Western Europe and the global market - Ajaya Kumar Panda; Swagatika Nanda (Financial Innovation, 2017)
Background: The present study examines the short term dynamics and long term equilibrium relationship among the stock markets of 17 countries in Western Europe as well as the world market, using time series techniques. Methods: Weekly returns of market benchmark indices of the respective countries are used from the second week of 1995 to the fourth week of December 2013. Results: The study finds that the market returns of Austria, Belgium, the Netherlands, and France are relatively less dynamically interlinked as compared with Britain, Denmark, Finland, Germany, Portugal, Spain, Sweden, Switzerland, Greece, Ireland, Luxembourg, and Norway, which are quite dynamically interlinked within the region as well as with the MSCI world index. Conclusion: There exists a strong long run equilibrium relationship between the return distributions of the stock markets within the region.
Keywords: C22; F36; G15; 650; Stock market interlinkages; Cointegration; VAR; VECM; MSCI